Ecoexplore Development through Augmented Reality on Ecosystem Topics to Improve Students' Visual Literacy - Shinta Bella; Sulasfiana Alfi Raida (Pro-Life, 2025)
Development of Ecoexplore (explore nature) through Augmented Reality (AR) on ecosystem material to improve students' visual Literacy. In today's digital era, science learning requires an approach that is more interesting and closer to the real world of students. This research aims to develop an interactive learning media, Ecoexplore, based on Augmented Reality (AR), combined with an approach to exploring the natural environment, particularly focusing on ecosystem materials. The method used is Research and Development (R&D) with the ADDIE model. This media was validated by experts and tested on teachers and junior high school students. The validation results indicate that Ecoexplore is highly feasible to use, and the user response is also very positive. The findings show that using AR technology linked to students' real-life experiences can improve visual literacy and make the learning process more fun, interactive, and meaningful. Moreover, Ecoexplore encourages students to observe and analyze ecosystem components concretely, fosters curiosity, supports active participation, and strengthens connections between theory and practice in science learning.